An Ultra-Low-Friction Triboelectric–Electromagnetic Hybrid Nanogenerator for Rotation Energy Harvesting and Self-Powered Wind Speed Sensor - Wang, Peihong; Pan, Lun; Wang, Jiyu; Xu, Minyi; Dai, Guozhang; Zou, Haiyang; Dong, Kai; Wang, Zhong Lin (ACS nano, 2018)
Triboelectric nanogenerators (TENGs) are attracting more and more attention since they can convert various mechanical energies into electric energy. However, in traditional TENGs for harvesting rotation energy, most of the contacts between two triboelectric materials are rigid-to-rigid contact with very large friction force, which limits their practical application. Here, we report an ultra-low-friction triboelectric–electromagnetic hybrid nanogenerator (NG). A freestanding mode TENG and a rotating electromagnetic generator (EMG) are integrated together to realize the complementary individual merits. The very soft and elastic contact between the two triboelectric materials in the TENG results into very small friction force. The influences of the type and the dimensions of the dielectric material on the performance of the TENG are studied systematically from theory to experiments. The results indicate that the open-circuit voltage and the transfer charge of the TENG increase with the rotation speed, which is very different from a traditional rotary TENG and is due to the increase of the contact area. The optimized TENG has a maximal load voltage of 65 V and maximal load power per unit mass of 438.9 mW/kg under a speed rotation of 1000 rpm, while the EMG has a maximal load voltage of 7 V and maximal load power density of 181 mW/kg. This demonstration shows that the hybrid NG can power a humidity/temperature sensor by converting wind energy into electric energy when the wind speed is 5.7 m/s. Meanwhile, it can be used as a self-powered wind speed sensor to detect wind speed as low as 3.5 m/s.